Altered Prefrontal Blood Flow Related With Mild Cognitive Impairment in Parkinson's Disease: A Longitudinal Study - Wang, Jian; Zhang, Wei; Zhou, Ying; Jia, Jia; Li, Yuanfang; Liu, Kai; Ye, Zheng; Jin, Lirong (Frontiers in Aging Neuroscience, 2022)
Cognitive impairment is a common nonmotor symptom in Parkinson’s disease (PD), with executive dysfunction being an initial manifestation. We aimed to investigate whether and how longitudinal changes in the prefrontal perfusion correlate with mild cognitive impairment (MCI) in PD patients. We recruited 49 PD patients with normal cognition and 37 matched healthy control subjects (HCs). PD patients completed arterial spin labeling MRI (ASL-MRI) scans and a comprehensive battery of neuropsychological assessments at baseline (V0) and two-year follow-up (V1). HCs completed similar ASL-MRI scans and neuropsychological assessments at baseline. At V1, ten PD patients progressed to MCI (converters) and thirty-nine patients remained cognitively normal (nonconverters).We examined differences in cerebral blood flow (CBF) derived from ASL-MRI and neuropsychological measures (a) between PD patients and HCs at V0 (effect of the disease), (b) between V1 and V0 in PD patients (effect of the disease progression), and (c) between converters and nonconverters (effect of the MCI progression) using t-tests or ANOVAs with false discovery rate correction. We further analyzed the relationship between longitudinal CBF and neuropsychological changes using multivariate regression models with false discovery rate correction, focusing on executive functions. At V0, no group difference was found in prefrontal CBF between PD patients and HCs, although PD patients showed worse performances on executive function. At V1, PD patients showed significantly reduced CBF in multiple prefrontal regions, including the bilateral lateral orbitofrontal, medial orbitofrontal, middle frontal, inferior frontal, superior frontal, caudal anterior cingulate and rostral anterior cingulate. More importantly, converters showed a more significant CBF reduction in the left lateral orbitofrontal cortex than nonconverters. From V0 to V1, the prolonged completion time of Trail Making Test-B (TMT-B) negatively correlated with longitudinal CBF reduction in the right caudal anterior cingulate cortex. The decreased accuracy of the Stroop Color-Word Test positively correlated with longitudinal CBF reduction in the left medial orbitofrontal cortex. In addition, at V1, the completion time of TMT-B negatively correlated with CBF in the left caudal anterior cingulate cortex. Our findings suggest that longitudinal CBF reduction in the prefrontal cortex might impact cognitive functions (especially executive functions) at the early stages of PD.